지역거점 공공병원의 의료서비스 질과 고객충성도와의 관계 - 이진우(Jin-Woo Lee) (한국콘텐츠학회 논문지, 16(12), 2016)
This study is significant for its proposed health care quality improvement methods to study the relationship between the medical service quality and customer loyalty in the regional hub public hospital. The subjects were selected 604 people who visited the regional hub public hospital to customers from June 9 to June 30, 2014 as the final survey. The analysis was conducted hierarchical regression analysis to identify factors affecting the reliability factor analysis and customer loyalty. In conclusion showed that accessibility factors affecting customer loyalty, awareness hospital, the perceived value of cost-effectiveness, human services on a significant impact. The regional hub public hospitals by focusing efforts I have a continuity of customer care through constant management in order to provide quality health care, increase the frequency of use and loyalty are needed. 본 연구는 지역거점 공공병원의 의료서비스 질과 고객충성도와의 관계를 연구하여 의료서비스 질의 향상 방안을 제시하는데 그 의의가 있다. 조사대상자는 2014년 6월 9일부터 6월 30까지 지역거점 공공병원을 내원한 고객들로 604명을 최종 조사대상으로 선정하였다. 분석방법은 신뢰도 및 요인분석과 고객충성도에 영향을 미치는 요인을 파악하기 위하여 위계적 회귀분석을 실시하였다. 결론을 보면 고객충성도에 영향을 미치는 요인으로 접근성, 병원인지도, 지각 된 비용효과 가치, 인적서비스가 유의한 영향을 미치는 것으로 나타났다. 앞으로 지역거점 공공병원이 양질의 의료서비스를 제공하기 위해서는 지속적인 관리를 통해 고객관리의 연속성을 가지는데 집중함으로써 이용빈도와 충성도를 높이기 위한 노력이 필요하다.